Análisis del factor beta ( β) en el modelo de amplitud - Hernández R., José G. (2003)
In a recent work a model appeared to help to the decision making under uncertainty, whose main characteristic is that this model, beyond which they make the models traditional, takes into account the dispersion. This model, The Amplitude Model (TAM) [El Modelo de Amplitud (EMA)], consists basically of evaluating the expected values of the alternatives and correcting these values when taking into account the dispersion of the payments.  It is working with the amplitude, due to its simplicity and facility of application. When doing use of the dispersion in the model was necessary the construction of a factor beta (β), which is used indeed to punish the amplitude. In order to validate the model it was proven with some particular problems in his majority, taken from specialized Literature, being seated his applicability, but simultaneously the rank of variation of the factor noticed that beta (β), did not seem to have sense that was from zero to one, as it settled down at first, thus as recommendation of this research emerge out, that will analyze with greater depth the rank of beta variation (β).  With this research the result of this study appears, for which the scientific method applied to research operations, where first the problem was defined, which can be transcribed like the objectives of the investigation: To analyze the variability of the factor beta (β), in the applications of The Amplitude Model (TAM), so that the results obtained with their application do not lose physical sense.